2012
DOI: 10.3389/fpsyg.2012.00019
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Antifaces and the Perception of Correct Famous Identity in an Average Face

Abstract: Previous experiments have examined exposure to anti-identities (faces that possess traits opposite to an identity through a population average), finding that exposure to antifaces enhances recognition of the plus-identity images. Here we examine adaptation to antifaces using famous female celebrities. We demonstrate: that exposure to a color and shape transformed antiface of a celebrity increases the likelihood of perceiving the identity from which the antiface was manufactured in a composite face and that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 46 publications
0
14
1
Order By: Relevance
“…The findings by Little et al (2012) are in potential contrast with a series of recent experiments suggesting that although shape does play a role in the initial encoding of unfamiliar faces, shape is remarkably unimportant in the recognition of familiar faces (Hole, George, Eaves, & Rasek, 2002;Kaufmann, Schulz, & Schweinberger, 2013;Kaufmann & Schweinberger, 2008).…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…The findings by Little et al (2012) are in potential contrast with a series of recent experiments suggesting that although shape does play a role in the initial encoding of unfamiliar faces, shape is remarkably unimportant in the recognition of familiar faces (Hole, George, Eaves, & Rasek, 2002;Kaufmann, Schulz, & Schweinberger, 2013;Kaufmann & Schweinberger, 2008).…”
Section: Discussioncontrasting
confidence: 80%
“…However, since their face-morphing algorithm used alterations in both shape and reflectance, they did not demonstrate that their effects of anti-face adaptation reflected an altered perception of shape specifically. A more recent study by Little et al (2012) investigated the recognition of celebrities' faces that were preceded by different kinds of anti-faces that could be (1) shape and reflectance-transformed (as in Leopold et al, 2001), (2) had average reflectance but were shape-transformed to form an anti-shape image, or (3) had average shape but were reflectancetransformed to form an anti-reflectance image. Little et al found that anti-shape adaptors had a stronger effect on identity recognition than anti-reflectance adaptors, supporting Leopold´s original interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This highlights the importance of ruling out lower-level explanations when considering face aftereffects, especially since aftereffects can occur at any level of the visual pathway (Thillman and Webster, 2012). More generally, Little et al (2012) have shown that the FIAE is primarily based on face shape information rather than color information.…”
mentioning
confidence: 93%
“…Little et al (2012) have shown that these aftereffects are equivalent for laboratory based studies and studies conducted on the internet. These authors also noted that the aftereffects were stronger during the earlier trials during the post-adaptation test.…”
mentioning
confidence: 94%